PARAMETRI PSIHOLOGICI AI LECTURII ȘI INTERPRETĂRII OPERELOR LITERARE - Constantin ŞCHIOPU (Moldova State University, 2020)
În articol se face referință la o serie de factori psihologici, care determină lectura și interpretarea operei literare: competențele lingvistică, literară, culturală, înzestrările imaginativă, asociativă, senzorială, empatică, emoţională, proiectivă, opiniile, credinţele şi atitudinile personale ale cititorului/ interpretului, orizontul lui de așteptare. În această ordine de idei sunt actualizate câteva teorii cu privire la lectura și receptarea operei literare: caracterul structural al operei literare (H.Markiewicz), orizontul de așteptare (H-R. Jauss), formarea competențelor (P.Cornea), cititorul - coparticipant la actul de creație (J.P.SartrE). Totodată, în funcție de acești parametri psihologici, sunt propuse mai multe sugestii metodologice referitoare la interpretarea operei literare.   PSYCHOLOGICAL PARAMETERS OF THE READING AND INTERPRETATION OF LITERARY WORKS The article refers to a series of psychological factors which determine the reading and interpretation of the literary work: linguistic, literary, cultural competences, the imaginative, associative, sensorial, empathic, emotional and projective endowments, opinions, beliefs and personal attitudes of the reader/interpreter, their expectation horizon. Therefore, some theories on the reading and reception of the literary work have been updated: the structural character of the literary work (H.Markiewicz), the horizon of expectation (H.R.Jauss), the training of competences (P.Cornea), the reader - a participant in the creative act (J.P.Sartre). Hence, depending on these psychological parameters, several methodological suggestions regarding the interpretation of the literary work are proposed.